Feasibility of a clinic-delivered adolescent and pediatrician communication intervention on patient participatory behaviors and behavior change: TIC TAC pilot study. Issue 2 (February 2020) - Pollak, Kathryn I.; Gao, Xiaomei; Chung, Richard J.; Farrell, David; Bravender, Terrill
Highlights: Pediatricians only can influence adolescents to adopt or keep healthy patterns. Adolescents need to be prepared to engage fully in conversations with pediatricians. Time is a central barrier to pediatricians addressing high-risk behaviors. Feedback Guides with communication tips can promote engaged conversations. Having engaged conversations can possibly help promote behavior change. Abstract: Objectives: Pediatrician-adolescent communication can improve adolescent health. We conducted a two-arm design to pilot-test an intervention that randomized adolescents to receive a Feedback Guide to promote engaged conversations. We hypothesized that adolescents who received the Guide would be more participatory. Methods: We recruited 12 pediatricians and 29 adolescents. Clinic staff enrolled adolescents using a tablet that enabled consenting, assessment of high-risk behaviors, and audio recording of encounters. We surveyed adolescents immediately and two months after the encounter. Results: Adolescents who received the intervention were more participatory than adolescents who did not. Pediatricians counseled on 20 of 32 high-risk behaviors with no significant arm differences. At follow-up, adolescents changed 9 of 32 behaviors; 6 were among 4 of adolescents in the intervention arm. Adolescents in the intervention arm were also more likely to report that counseling would help them change their behavior; these encounters were slightly longer than control arm encounters. Conclusions: We confirmed feasibility of a streamlined approach to enrolling and audio recording encounters. The Feedback Guide improved adolescent participation and might have helped them adopt healthier behaviors. Practice Implications: Adolescents can be primed to be participatory and can change their behaviors after a meaningful encounter with their pediatrician.